GENEALOGY OF THE AKUSHIN QADIS IN THE LIGHT OF NEWLY SOURCES - Ajtberov, Timirlan Magomedovic; Aliev, Bagomed Gadaevic (History, Archeology and Ethnography of the Caucasus, 2023)
The article introduces new epigraphic Arabic-language sources on the history of Akusha, revealed among the genealogical records and colophons of manuscripts. The new sources substantially supplement the information about the qadis of Akusha, and in some cases make it possible to radically revise the existing scientific ideas about the genealogical ties of the qadis of Akusha-Dargo. In the second half of the 19th century, an officer of the tsarist army A.V. Komarov was the first to suggest the existence in certain territories of Dagestan of the institution of hereditary qadis, who either had already became qadi-emirs, “spiritual princes”, or had a tendency to turn into such. He localized the presence of such an institution in the northern part of Tabasaran, which adjoined Derbent from the west, and in the Akusha union of communities. In 1986, one of the authors of this article, B.G. Aliev, compiled a list of Akushin qadis on the basis of Russian sources, A.R. Shikhsaidov’s works and field material. For several decades, this list has been of great help in the study of the political history of the region. In the light of new data, the authors raise questions regarding the chronology of the Akushin qadis in power and question the information of A.V. Komarov. The authors introduce new data on the chronology of Akushin qadis’ stay in power, on the existence of the institution of hereditary of Akushin qadis in the 17th – early 19th centuries, in the inheritance of the mentioned title within one Akushin clan, and even more so, within one family. The authors admit that by the middle of the 18th century there was a tendency among the qadis of Akusha to turn into the likeness of the qadis-princes of Northern Tabasaran, but the “Dargin” elite of the late 18th century did not approve it. The article provides general information about Akusha, a detailed historiography of the issue of Akushin qadis, a review of new sources and the conclusions of the authors. When writing this article, a comparative method was applied.